Still a Target Sexual Diversity and Power of Caring - Konishi, Chiaki (School Psychology International, 2013)
This study examined the link between victimization and sexual orientation and how this link contributes to social-emotional health, extending to school-related outcomes among adolescents. Of additional interest was to explore the role of having caring adult support as a protective factor to reduce the risk for high levels of distress or enhance positive aspects of life experiences. Participants included 27,245 students (14,114 girls) in grades 7-12 in Western Canada. Results of logistic regression revealed that Lesbian/Gay/Bisexual youth who had experiences of being victimized were at greatest risk for social-emotional and school-related problems, including educational aspiration and activity engagement. Our results also showed that having caring support from parent or teacher significantly contributed to reducing the likelihood of experiencing social-emotional and educational difficulties even among victimized sexual minority students as well as heterosexual youth